Studies on Drip Irrigation and Nitrogen Management in Gladiolus (Gladiolus grandiflorus L.) - Thentu, T. L.; Dutta, D.; Dutta Mudi, D.; Saha, A. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted at Central Research Farm of Bidhan Chandra Krishi Viswavidyala, Gayespur, West Bengal during the winter seasons of 2012-2013 and 2013-2014 to study the effect of drip and surface irrigation in gladiolus with different sources of nitrogen management. The experiment was laid out in split-plot design replicated thrice. Main plot treatments consist of four levels of irrigation such as surface irrigation with IW:CPE 1.0 and three drip irrigation at 1.0, 0.8 and 0.6 of crop-evapotranspiration (ETc), and three nitrogen sources like 100% N through vermicompost, 50% N through vermicompost+50% N through inorganic fertilizer and 100% N through inorganic fertilizer in sub-plots. The results showed that drip irrigation at 0.8 ETc showed significantly higher plant height, number of spikes plot-1, florets spike-1, spike length, spikeweight and spike yield, which was at par with drip irrigation at 1.0 ETc. Minimum yield attributes and spike yield was obtained withdrip irrigation at 0.6 ETc. Similarly, higher plant variables and spike yield was noticed with 50% inorganic N+50% organic N as vermicompost. However, drip irrigation at 0.6 ETc with 50% inorganic N plus 50% organic N recorded the maximum water use efficiency. The interaction effect showed that drip irrigation at 0.8 ETc along with integrated nitrogen management (50% inorganic N+50% organic N) showed significantly higher spike yield. The highest gross returns, net returns and benefit: cost ratio were recorded with drip at 0.8 ETc and integrated sources of nitrogen (50% inorganic N+50% organic N).